Spectrum of mutations and sequence variants in the FALDH gene in patients with Sjögren-Larsson syndrome - Sillén, Anna; Anton-Lamprecht, Ingrun; Braun-Quentin, Cordula; Kraus, Cornelia S.; Sayli, Bekir Sitki; Ayuso, Carmen; Jagell, Sten; Küster, Wolfgang; Wadelius, Claes (Human mutation, 1998)
The gene encoding the human fatty aldehyde dehydrogenase (FALDH) is located on 17p11.2, causing Sjögren-Larsson syndrome (SLS) when mutated. SLS is an autosomal recessive disorder characterized by a combination of mental retardation, congenital ichthyosis, and spastic di- or tetraplegia. We report here on studies of 16 SLS families from Europe and the Middle East, which resulted in identification of 11 different mutations. The spectrum of mutations characterized in the present study are five nucleotide substitutions resulting in amino acid changes, five frameshift mutations introducing a stop codon, and one in-frame deletion with insertion at the same position. We also observed silent sequence variants in the FALDH gene and a base pair substitution in exon 5 that alters aspartic acid to asparagine, all of which are considered polymorphisms. Hum Mutat 12:377-384, 1998. © 1998 Wiley-Liss, Inc.